Aromatics from Beechwood Organosolv Lignin through Thermal and Catalytic Pyrolysis - Konstantinos G. Kalogiannis; Leonidas Matsakas; Angelos A. Lappas; Ulrika Rova; Paul Christakopoulos (Energies, 2019)
Biomass fractionation, as an alternative to biomass pretreatment, has gained increasing research attention over the past few years as it provides separate streams of cellulose, hemicellulose, and lignin. These streams can be used separately and can provide a solution for improving the economics of emerging biorefinery technologies. The sugar streams are commonly used in microbial conversions, whereas during recent years lignin has been recognized as a valuable compound as it is the only renewable and abundant source of aromatic chemicals. Successfully converting lignin into valuable chemicals and products is key in achieving both environmental and economic sustainability of future biorefineries. In this work, lignin retrieved from beechwood sawdust delignification pretreatment via an organosolv process was depolymerized with thermal and catalytic pyrolysis. ZSM-5 commercial catalyst was used in situ to upgrade the lignin bio-oil vapors. Lignins retrieved from different modes of organosolv pretreatment were tested in order to evaluate the effect that upstream pretreatment has on the lignin fraction. Both thermal and catalytic pyrolysis yielded oils rich in phenols and aromatic hydrocarbons. Use of ZSM-5 catalyst assisted in overall deoxygenation of the bio-oils and enhanced aromatic hydrocarbons production. The oxygen content of the bio-oils was reduced at the expense of their yield. Organosolv lignins were successfully depolymerized towards phenols and aromatic hydrocarbons via thermal and catalytic pyrolysis. Hence, lignin pyrolysis can be an effective manner for lignin upgrading towards high added value products.